The AGT and AGTR1 polymorphisms and their contribution to performance-related phenotypes - Gineviciene, V.; Jakaitiene, A.; Milasius, K.; Tubelis, L.; Kucinskas, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Among the individual components of renin-angiotensin system (RAS), the genes encoding angiotensinogen(AGT) and angiotensin- II receptor typeI (AGTR1) together with environmental factors play important role in physiological process. The significance of AGT C/T (C704T, Tre235Met) and AGTR1 A/C (3 UTR A1166C) polymorphisms is unknown in physical performance, anthropometric features, and for body composition in a population of athletes participating in different disciplines. Methods: A total of 164 Lithuanian elite athletes (77endurance-oriented, 38power-oriented, 49 mixed group ) and 240 healthy unrelated citizens (controls) were genotyped (PCR-RFLP). Vertical jump (counter-movement) test was used for the estimation of the short-term explosive muscle power(STEMP). Anaerobic alactic maximum power(AAMP) was estimated by the stair climbing test. Aerobic capacity function was determined using the maximum oxygen consumption(VO2max). Anthropometric measures were also estimated. Results: There were no significant allele or genotype frequency differences between the athletes groups and the controls. The height, weight, muscle mass, handgrip strength and indices of functional capacity STEMP, AAMP and VO2max were significantly different with respect to gender (p<0.05). Regression analysis for total athletes group showed that gender, fat mass and muscle mass have significant impact on AAMP (R2=0.575). The high muscle mass and low fat mass of an athlete lead to improved AAMP. There as STEMP and muscle mass (positive) are important describing AGTR1 A/C genotype (R2=0.421). High STEMP was observed of AGTR1 A/A genotype for men and of AGTR1 A/C genotype for women in speed/power-oriented sports. VO2max of athletes with AGTR1 A/A genotype was higher than of those carrying AGTR1 A/C and C/C genotypes (p<0.05). Discussion: Reports on the RAS polymorphisms have to date focused on the AGT T allele and AGTR1 C allele, and its association with pathological events (cardiovascular complications). In the study, we employ an alternative way where the significance of AGT(C/T) and AGTR1(A/C) is accessed via their physiological effects in athletes. Statistical significance was reached for AGTR1(A/C) but not for AGT(C/T) polymorphism. We found that the influence of AGTR1 polymorphism on the physical capacity phenotype is different depending on gender and associated ith a complex phenotypic characteristic. The athletes, carriers of the AGTR1 A/A genotypes, typically have better VO2max (aerobic capacity) as well as have better ability to achieve high muscle capacity indices when exercising short-term explosive muscle power tasks. Summarizing the results we conclude that in the Lithuanian athletes the AGTR1 genotypes show unique characteristics and the A allele of the AGTR1 might influence general sporting prowess.